Lipemia Interferences in Biochemical Tests, Investigating the Efficacy of Different Removal Methods in comparison with Ultracentrifugation as the Gold Standard - Neda Soleimani; Sahand Mohammadzadeh; Fateme Asadian (Journal of Analytical Methods in Chemistry)
Introduction. As a common interferer in clinical chemistry, lipemic specimens could be a source of significant analytical errors. Ultracentrifugation has been by far the only reliable, but an unavailable and expensive, method to eliminate the lipemic effect. Materials and Methods. Among the daily samples, those with triglyceride >400 mg/dL (4.6 mmol/L) and also turbid were selected, divided into three groups, based on triglyceride concentration, and three pooled serums were made for each group. Then all pooled serums were investigated by using a DIRUI biochemistry analyzer CS-800 for routine chemistry tests in different methods including direct measurement, serum blank, serum dilution, and measurement after ultracentrifugation. Results. According to our study, there were significant differences before and after ultracentrifugation in all lipemic levels and for all parameters except for alanine aminotransferase (ALT), alkaline phosphatase (ALP), bilirubin, and uric acid. Based on allowable inaccuracy for each parameter, calcium, magnesium, phosphorus, total protein, iron, total iron-binding capacity (TIBC), urea, and chloride are being influenced by all lipemic degree and neither serum dilution nor using serum blank is as effective as ultracentrifuge for elimination. Serum blank was a proper method of lipid removal for the measurement of glucose. Conclusion. Lipemia is a well-known interferer in clinical chemistry. One cannot avoid lipemia, but fortunately, severe lipemia is a rare phenomenon in the laboratory, and for assessment of some analytes in a lower degree of lipemia, use of serum blank eliminates the need for ultracentrifuge.